ANALISIS POLA PERILAKU GENDER PADA MASYARAKAT KELAYU KABUPATEN LOMBOK TIMUR - Baiq Fitri Rahmawati (Universitas Hamzanwadi, 2014)
The aims of study is to describe the pattern of gender behavior in Kelayu society by comparing patterns of gender behavior in housewife’s family with mother work’s family, and to analyze the differences between them. The method of research use a qualitative method with the techniques of data collection such as interviews, observation and documentation. Meanwhile, the techniques of data analysis used Milles and Hubberman’s techniques is data reduction, data display, dan conclusion drawing/verification. The results of this study showed a pattern of gender behavior in society Kelayu as follows: (1) Men are the breadwinners and women are housekeeper. (2) Aggressiveness is male. With the aggressive nature allows men to access the wealth and social status in the community; (3) Respect and obedience of the woman. Women are required to have a high adherence properties, especially adherence to her husband and their parents.; (4) a high activity level is male. Men have a higher level of activity than women, since small socialized in the forms of the game. They do a lot of outdoor activities, such as playing the game wide cap pistol, kites, and many other activities that require a lot of motion and outside the home; and (5) Women have a passive nature and soft, gentle and loving, so it is reasonable given the task of parenting. Weak women makes it requires protection from men. Keywords: behavioral patterns of gender, ancestry housewife, mother's family work